Zinc supplementation for reducing duration and severity of acute diarrhoea in children: a meta-analysis - D. Parikh, Dhyey; M. Zalavadia, Parit; Patel, Jimish; Panchal, Harshal; M. Patel, Neha; Khan, Afrin; Rai, Ahana (International Journal of Research in Medical Sciences, 2025)
Acute diarrhoea remains a major cause of morbidity and mortality among children under five years, particularly in low- and middle-income countries, despite widespread use of oral rehydration therapy. Zinc supplementation has been endorsed by international health authorities as an adjunct therapy, yet variations in its reported efficacy necessitate an updated synthesis of available evidence. This meta-analysis evaluated the impact of zinc supplementation on the duration and severity of acute diarrhoea in children aged 0–59 months. A systematic literature search was conducted in PubMed, Embase, and Web of Science databases for randomized controlled trials published between January 2000 and June 2025 comparing zinc supplementation with placebo or standard treatment. Fifteen eligible trials comprising 8,423 participants were included, and pooled estimates were calculated using a random-effects model. Zinc supplementation significantly reduced the mean duration of diarrhoea by 0.72 days (95% CI: −1.04 to −0.40) and decreased the risk of diarrhoea persisting beyond seven days (RR=0.65; 95% CI: 0.50–0.85). Furthermore, the risk of diarrhoea-related hospitalization was lower in the zinc group (RR=0.74; 95% CI: 0.60–0.92). Moderate heterogeneity (I²=62%) was observed across studies, likely reflecting variations in population characteristics, zinc formulations, and baseline nutritional status. These findings confirm that zinc supplementation effectively reduces both the duration and severity of acute diarrhoea in young children and supports existing World Health Organisation (WHO) recommendations for its routine use in diarrhoeal disease management. Broader integration of zinc supplementation into national child health programs, especially in resource-limited settings, could substantially reduce the global burden of childhood diarrhoeal disease.